The Influence of Financial Literacy, Financial Behavior and Financial Technology on Investment Decisions through Locus of Control (Financial Management Literature Review) - Sanjaya, Willy (Dinasti International Journal of Digital Business Management, 2023)
Literature Review Article on the Effects of Financial Literacy, Financial Behavior and Financial Technology on Investment Decisions through Locus of Control through Locus of Control is a scientific article that aims to build a research hypothesis on the influence of inter-variables to be used in further research , within the scope of Financial Management. The method of writing this Literature Review article is the library research method , which is sourced from online media such as Google Scholar, Mendeley and other academic online media . The results of this article are that: 1) Financial Literacy affects Investment Decisions through Locus of Control; 2) Financial Behavior influences Investment Decisions through Locus of Control; and 3) Financial Technology affects Investment Decisions through Locus of Control. Apart from these 3 exogenous variables that influence the endogenous investment decision variables through Locus of Control there are many other factors including motivational variables, macroeconomics and risk profiles.